The epidemiology of oro-nasal haemorrhage and suffocation in infants admitted to hospital in Scotland over 10 years. Issue 10 (6th July 2010) - McIntosh, N; Mok, J Y Q; Margerison, A; Armstrong, L; Mathews, A; Robertson, A K; Street, J; Sweeney, S; Chalmers, J
Abstract : Objective: To estimate the incidence of oro-nasal haemorrhage (ONH) and suffocation in infancy and to investigate their aetiology and overlap. Setting: A 10-year retrospective hospital based study from Scotland, UK. Methods: The hospital notes of all infants presenting with ONH or suffocation identified through the Information Services Division of the Scottish Health Service were reviewed by three paediatric consultants, two with child protection expertise. The hospital-based incidences of haemorrhages from different sites were calculated and the causes ascertained. When trauma was involved, a decision was made whether it was likely to have been accidental. Results: 7 cases of suffocation and 88 of ONH were recorded at hospital discharge over 10 years. This gives an incidence of ONH of 1.62 (1.30 to 1.99)/10 000 live births (95% CI) which consists of haemorrhage arising from nose or mouth (N/M), n=65 (1.19/10 000 (0.92 to 1.52)); haematemesis, n=11 (0.20/10 000 (0.10 to 0.36)); haemoptysis, n=3 (0.06/10 000 (0.1 to 0.16)) and pulmonary haemorrhage, n=9 (0.17/10 000 (0.08 to 0.31)). No suffocation cases were recorded as having a coincident ONH, but five ONH cases were probably caused by airway obstruction. 40 of 65 cases of N/M were associated with trauma, which in 15 cases were thought to be probable abuse; four were associated with coagulation abnormalities. 2/3 haemoptysis cases, 2/11 haematemesis cases and 8/65 N/M cases were associated with a coincident respiratory tract infection, though in 4/8 of these cases, there was an associated apparent life-threatening event. Conclusions: Haemorrhage from the N/M is rare in infancy. Trauma is commonly involved and child protection concerns often poorly explored. Pulmonary haemorrhage and several cases of ONH were associated with probable airway obstruction. Information, in cases of ONH, is in general recorded badly, and an investigation and management plan are suggested.